Reconstituting the constitution - Morris, Caroline 1973-; Boston, Jonathan 1957-; Butler, Petra, |d 1966- (Springer Berlin Heidelberg Imprint: Springer, 2011)
In this volume, scholars, practitioners, politicians, public officials, and young people explore these questions and others in relation to the New Zealand constitution and provide some thought-provoking answers. This book is recommended for anyone seeking insight into how a former British colony with bicultural foundations is making the transition to a multicultural society in an increasingly complex and globalized world.